Northwest Africa 5958: A weakly altered CM‐related ungrouped chondrite, not a CI3. (9th March 2016) - Jacquet, Emmanuel; Barrat, Jean‐Alix; Beck, Pierre; Caste, Florent; Gattacceca, Jérôme; Sonzogni, Corinne; Gounelle, Matthieu
Abstract: Northwest Africa (NWA) 5958 is a carbonaceous chondrite found in Morocco in 2009. Preliminary chemical and isotopic data leading to its initial classification as C3.0 ungrouped have prompted us to conduct a multitechnique study of this meteorite and present a general description here. The petrography and chemistry of NWA 5958 is most similar to a CM chondrite, with a low degree of aqueous alteration, apparently under oxidizing conditions, and evidence of a second, limited alteration episode manifested by alteration fronts. The oxygen isotopic composition, with ∆' 17 O = −4.3‰, is more 16 O‐rich than all CM chondrites, indicating, along with other compositional arguments, a separate parent body of origin. We suggest that NWA 5958 be reclassified as an ungrouped carbonaceous chondrite related to the CM group.